Tsardom of Muscovy Traditional Culture and Peter's Westernization Project - T. V. Chernikova (Vestnik MGIMO-Universiteta, 2022)
The article studies Peter the Great “revolutionary” westernization project of Russia by reviewing the most significant differences in the socio-cultural system of Russia centuries compared to its Western European counterparts in the second half of the 15th – early 18th century. The first part of the article identifies the distinctive features of the socio-cultural system of Russia, which the observers from the Western European saw as the most different from the “correct” European norms and institutions in the second half of the 15th-16th centuries. The most distinctive feature was the concentration in the hands of the Moscow sovereign not only of the state political power but also the property rights on all the country's resources. It resulted in the development of the public sphere in Russia along the line of “sovereign vs slaves”, which precluded the Renaissance Western political thought “to accept” Russia into “Europe”.The author examines two main Western description of Muscovy (Muscovia) in the 15th – 17th centuries: a benevolent approach adopted by Johannes Fabry, Paolo Giovio, Alberto Campense; and a critical approach taken by most authors analyzing Muscovy (Matvey Mekhovsky, Sigismund Herberstein, etc.). These two approaches were also reflected in the dispute between the jurists of the late 16th century about the legitimacy of the state power in Russia – “illegitimate tyranny” by Herberstein and Fletcher and “legitimate despotism” by Boden. These debates in RenaissanceEurope informed and shaped the concept of the patrimonial monarchy (patrimonial system) in Russia, which was subsequently developed by Russian influential historians (V.O. Klyuchevsky, P.N. Milyukov and others) and foreign experts (R. Pipes, E. Carrer d'Ancausse and others).The second half of the article analyzes the concept of “Europeanization” (“Westernization”) of Russia and offers a periodization of this phenomenon. The start of early Europeanization, when Russia began borrowing military, technical, cultural, and other innovations from Western Europe can be dated from the birth of a unified Moscow state. Peter's Westernization was indeed a new stage in adopting European experience because he removed the state and church barriers in the communication of Russian people with Western Europeans and encouraged not only going to the West for education and science, but also opened the way to the creation of secular education and science in Russia. These were prerequisites for the beginning of the modernization of Russia.In other matters, Peter's westernization differed from the previous periods only in the number of cultural and institutional adoptions. Peter’s political system was the apogee of the patrimonial culture in Russia.